2016
DOI: 10.1007/s10008-016-3268-6
|View full text |Cite
|
Sign up to set email alerts
|

Hollow mesoporous silica sphere-embedded composite separator for high-performance lithium-ion battery

Abstract: A high-performance composite separator based on hollow mesoporous silica spheres, poly(vinylidene fluorideco-hexafluoropropylene) (PVdF-HFP), and poly(ethylene terephthalate) nonwoven was explored as lithium-ion battery separator via a dip coating technique followed by a phase separation wet process. Systematical investigations including morphology characterization, porosity measurement, electrolyte wettability, thermal shrinkage testing, and cell performance examination are carried out. It is demonstrated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…Hollow mesoporous silica spheres (HMSS) with ordered mesopores and uniform size distribution have been utilized as a ceramic filler with a PVDF–HFP binder to coat a polyethylene terephthalate (PET) nonwoven fabric. [ 84 ] The obtained HMSS/PVDF–HFP@PET CPS has not only a good electrolyte‐philic surface but also a preferred porous structure, which is beneficial for Li + transportation. As a result, the η EU and η σ of the resulting CPSs are significantly improved, by 124% and 296.4%, respectively (code 1–25).…”
Section: Composite Polymer Separator For Conventional Li‐based Secondmentioning
confidence: 99%
“…Hollow mesoporous silica spheres (HMSS) with ordered mesopores and uniform size distribution have been utilized as a ceramic filler with a PVDF–HFP binder to coat a polyethylene terephthalate (PET) nonwoven fabric. [ 84 ] The obtained HMSS/PVDF–HFP@PET CPS has not only a good electrolyte‐philic surface but also a preferred porous structure, which is beneficial for Li + transportation. As a result, the η EU and η σ of the resulting CPSs are significantly improved, by 124% and 296.4%, respectively (code 1–25).…”
Section: Composite Polymer Separator For Conventional Li‐based Secondmentioning
confidence: 99%
“…HMSS/PVDF-HFP composite separators with improved porosity were developed; the presence of SiO 2 spheres created a well-developed microporous structure, leading to higher wettability and ionic conductivity [ 98 ].…”
Section: Poly(vinylidene Fluoride) and Its Copolymersmentioning
confidence: 99%
“…Although most of the research focuses mainly on the solid ceramic nanoparticles but their hydrophilic surface could not accommodate more electrolytes, so the researchers’ approach is to use hollow particles to hold electrolyte more efficiently and enhance the lithium ions movement through the tiny pores of the core-shell particles. Xiao, W. et al [95] coated hollow silica nanoparticles on the surface of a PET nonwoven mat with the dip coating method. They found that the three-dimensional micron size porous structure was formed on both sides of the fibrous separator and polar nature of hollow silica, PET and PVDF-HFP binder enhanced the electrolyte uptake due to affinity towards electrolyte.…”
Section: Inorganic Particle-coated Composite Membranesmentioning
confidence: 99%